Conjoint application of nano-urea with conventional fertilizers: An energy efficient and environmentally robust approach for sustainable crop production - Upadhyay, Pravin Kumar; Dey, Abir; Singh, Vinod Kumar; Dwivedi, Brahma Swaroop; Singh, Tarunendu; G. A., Rajanna; Babu, Subhash; Rathore, Sanjay Singh; Singh, Rajiv Kumar; Shekhawat, Kapila; Rangot, Meenakshi; Kumar, Pradeep; et al. (PloS one, 2023)
One of the biggest challenges to be addressed in world agriculture is low nitrogen (N) use efficiency (<40%). To address this issue, researchers have repeatedly underlined the need for greater emphasis on the development and promotion of energy efficient, and environmentally sound novel fertilizers, in addition to improved agronomic management to augment nutrient use efficiency for restoring soil fertility and increasing farm profit. Hence, a fixed plot field experiment was conducted to assess the economic and environmental competency of conventional fertilizers with and without nano-urea (novel fertilizer) in two predominant cropping systems viz ., maize-wheat and pearl millet-mustard under semi-arid regions of India. Result indicates that the supply of 75% recommended N with conventional fertilizer along with nano-urea spray (N 75 PK+nano-urea) reduced the energy requirement by ~8–11% and increased energy use efficiency by ~6–9% over 100% nitrogen through prilled urea fertilizer (business as usual). Furthermore, the application of N 75 PK+ nano-urea exhibited ~14% higher economic yields in all the crops compared with N 50 PK+ nano-urea. Application of N 75 PK+nano-urea registered comparable soil N and dehydrogenase activities (35.8 μg TPF g -1 24 hrs -1 across all crops) over the conventional fertilization (N 100 PK). This indicates that application of foliar spray of nano-urea with 75% N is a soil supportive production approach. More interestingly, two foliar sprays of nano-urea curtailed nitrogen load by 25% without any yield penalty, besides reducing the greenhouse gases (GHG) emission from 164.2 to 416.5 kg CO 2 -eq ha -1 under different crops. Therefore, the application of nano-urea along with 75% N through prilled urea is an energy efficient, environmentally robust and economically feasible nutrient management approach for sustainable crop production.